Laparoscopic cholecystectomy in Songklanagarind Hospital - S Ruangsin; T Wanasuwannakul; S Sangkhathat (Journal of Health Science and Medical Research (JHSMR), 2007)
Objective: To contribute our five years of experience of laparoscopic cholecystectomy in Songklanagarind Hospital and find out the risk factors of prolonged length of hospital stay. Material and Methods: A review of the hospital database of all the patients who underwent laparoscopic cholecystectomy between January 2001 and December 2005. Results: A total of 539 laparoscopic cholecystectomies were performed; the conversion rate was 23.19%. In the cases of successful laparoscopic surgery; patients the mean time for hospital stay was 5.23 days. Surgical site infection occurred in 9.67% of the cases and prophylactic antibiotics were used for 85.27% of the patients. Significantly, surgical wound infection was associated with the type of drain used and also obesity (p = 0.03, p < 0.001). Local injections of marcaine did not reduce the volume/quantity of narcotic used (p=0.236), and was found to very slightly increase the incidence of wound infection (p = 0.215). Prophylactic postoperative nausea and vomiting (PONV) did not reduce the incidence of severe PONV and medication used (p = 0.109). One patient had a common bile duct injury (0.28%). Conclusion: Laparoscopic cholecystectomy is a safe and feasible procedure. We have tried to improve the patient outcome through moving to a day care laparoscopic cholecystectomy surgical option.